The importance of indigenous freshwater foods for rural women - Gomese, Chelcia; Wate, Jillian Tutuo; Alfred, Joy Ellen; Sendo, Evelyn; Tefetia, Malachi; Tepai, Jocelyn; Maike, Patricia; Pitakaka, Priscilla; Ride, Anouk; Eriksson, Hampus (WorldFish, 2023)
The importance of indigenous freshwater foods for rural women in Guadalcanal Province, Solomon Islands A film has been produced by WorldFish in partnership with the Guadalcanal Provincial Government on the vital role of indigenous foods in the province. The film depicts an indigenous aquatic foods cooking competition for women in the Ghaobata ward in the north Guadalcanal region, Solomon Islands during the 2021 International Rural Women’s day celebrations, and reinforces that: • Indigenous foods are part of our culture, identity an daily practice, • Women grow, harvest and cook indigenous foods for the nutrition for families and next generations • Indigenous foods are under threat of being replaced with high imports of processed food which is high in sugar, salt and fat and lifestyle changes affecting food choices and preparation. • The environment where indigenous foods are sourced from are also under threat from environment degradation due to land-based activities, poor management and climate change. • By promoting indigenous foods and indigenous management of environments, our indigenous people can still enjoy indigenous foods.